Point placement of late vegetative stage nitrogen splits increase the productivity, N-use efficiency and profitability of tropical maize under decade long conservation agriculture - Nayak, Harisankar; Parihar, Chiter Mal; Mandal, Baidya N; Patra, K.; Jat, Shankar Lal; Singh, Raj; Singh, Vinod K; Jat, Mangi Lal; Garnaik, Suravi; Nayak, J; Abdallah, Ahmed M. (Elsevier, 2022)
The rising economic and environmental costs of mineral fertilizers associated with lower nutrient use efficiency, and the need to respond the limitations of N fertilization under residue retained condition of conservation agriculture (CA) motivate the research for alternative N placement methods. The third principle of CA, i.e., residue retention on the soil surface hinders the right placement of split applied nitrogen (N). To address this issue, we assessed the impact of three N placement methods, i.e., NPM1: both the N splits were surface band placed, NPM2: the first split of N was sub-surface point placed and second N split (late vegetative stage) was surface band applied, and NPM3: both the N splits were sub-surface point placed, under 4-long-term tillage and residue management (+R) options, i.e., permanent raised bed (PB+R), zero-till flat (ZT+R) conventional till flat (CT+R) and first time zero till flat sowing of the crop on last 10-year fallow land (FZT+R), in an on-going long-term study (since 2008) in maize for three consecutive years (2018–2020). Results showed that sub-surface point placement of both the N splits (NPM3) increased maize grain yield by 4.7, 7.0 and 6.0% (3-years mean basis) compared to NPM2, under CA-based PB, ZT, and FZT plots, respectively. The peak growth rate in the CA-based PB+R plot was advanced by 4-days with a 9.2% higher growth rate compared to CT+R. Similarly, the peak growth rate in NPM3 was 20% higher than NPM1 plots. The changes in soil properties under CA altered the crop growth behavior, while sub-surface point placement of split applied nitrogen (N) increased the grain N content and altered the peak growth rate of maize. The variability in maize grain yield was best described by cob length and number of cobs in long-term tillage and by cob length in N management plots. The cob length and grains per cob were increased by 4.8–8.7 and 8.6–12.8% under CA-based plots compared to CT+R, respectively. The amount of vegetative stage accumulated N remobilized to maize grain was 21.2% higher under PB+R compared to CT+R plots, while the N remobilization in NPM3 was 22.9% higher compared to NPM1 plots. Similarly, the contribution of reproductive stage N uptake to grain was 9–12% higher in CA-NPM3 compared to CT-NPM1 plots. Further, the early and vigorous growth of maize resulted in a higher accumulation of N and its remobilization to the grains in CA-based and N point placed plots. The sub-surface point placement of N (NPM3) resulted in a 12.8, 14.5 and 9.2% higher benefit-cost ratio compared to NPM1 plots in 11th (2018), 12th (2019) and 13th (2020) years of experimentation, respectively. Therefore, the present study visualizes the impact of a decade-long CA and efficient N management on crop growth behavior, N uptake and remobilization and crop productivity and water use efficiency. This study provides evidence to popularize this technology in the CA-systems of Indo-Gangetic Plains and other similar agro-ecologies.